Turtle boy - Wolkenstein, M. Evan (Delacorte Press, 2020)
Seventh-grader Will Levine isn't having a stellar year: His biology teacher is forcing him to return all the turtles he's collected from the marsh behind the school; he's being bullied for his small chin; and his rabbi has assigned him to visit a terminally ill boy, RJ, as part of his bar mitzvah community service project. At first, Will and RJ don't get along, but when RJ asks Will to complete his bucket list for him, Will sets out on a journey of self-discovery.